2021
DOI: 10.1136/bmjdrc-2021-002321
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exposure to antibiotics on the gut microbiome and biochemical indexes of pregnant women

Abstract: IntroductionExposure to antibiotics (ABX) during pregnancy can have a systematic effect on both fetal and maternal health. Although previous biomonitoring studies have indicated the effects on children of extensive exposure to ABX, studies on pregnant women remain scarce. To explore the effect on pregnant women of environmental exposure to ABX through accidental ingestion and identify potential health risks, the present study investigated 122 pregnant women in East China between 2019 and 2020.Research design a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…However, this study lacked a discussion on the specific concentrations of individual antibiotics. 87 Given that a large proportion of antibiotics entering the human body are excreted in urine, urine samples are easier to collect compared to blood and other biological materials, antibiotic levels in urine could serve as biomarkers for antibiotic exposure. 88 Most antibiotics that enter the human body are excreted in unchanged form as still-active compounds.…”
Section: Exposure Levels Of Pregnant Women To Antibiotics 421 Questio...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study lacked a discussion on the specific concentrations of individual antibiotics. 87 Given that a large proportion of antibiotics entering the human body are excreted in urine, urine samples are easier to collect compared to blood and other biological materials, antibiotic levels in urine could serve as biomarkers for antibiotic exposure. 88 Most antibiotics that enter the human body are excreted in unchanged form as still-active compounds.…”
Section: Exposure Levels Of Pregnant Women To Antibiotics 421 Questio...mentioning
confidence: 99%
“…The findings identified six categories of antibiotics (sulfonamides, quinolones, tetracyclines, lincosamides, β-lactams, and amide alcohol antibiotics) in plasma, with a detection rate of 17.2%. However, this study lacked a discussion on the specific concentrations of individual antibiotics . Given that a large proportion of antibiotics entering the human body are excreted in urine, urine samples are easier to collect compared to blood and other biological materials, antibiotic levels in urine could serve as biomarkers for antibiotic exposure .…”
Section: Antibiotics In Pregnant Women and Fetusesmentioning
confidence: 99%
“…Enterobacteriaceae are also known to be pro-inflammatory, meaning the overgrowth of these populations could result in gut inflammation [75]. Tetracyclines, like all antibiotics, can affect the beneficial bacteria that make up the gut microbiome [39,76]. This can lead to a decrease in gut microbiome diversity, which has been linked to a range of health problems, including inflammatory bowel disease, obesity, and type 2 diabetes.…”
Section: Tetracycline Effects On the Gut Microbiomementioning
confidence: 99%
“…Most commonly, they are prescribed oral antibiotics for the treatment of skin, urinary, respiratory, and ear infections, although prescribing antibiotics without a clear clinical indication is not uncommon during pregnancy [ 12 ]. The gastrointestinal microbiota ecosystem, which is believed to contribute to the regulation of mood and emotion [ 13 ], is altered by antibiotics [ 14 ], including during pregnancy [ 15 ]. Prior studies have identified a potential link between antibiotic exposure and the development of depression [ 16 ], including one study by Field et al [ 17 ] that explored it as a risk factor for antenatal depression.…”
Section: Introductionmentioning
confidence: 99%